Determinan Persepsi Mengenai Etika Atas Penggelapan Pajak (Tax Evasion)(Studi pada Dosen di Universitas Muhammadiyah Surakarta - Rohmawati, Fitria Riski; , Dra. Mujiyati, M.Si (2017)
This study is aimed to examine the factors influencing the ethical perception towards tax evasion. The number of samples in the study were 84 lecturer at Muhammadiyah University of Surakarta. The sampling technique in the study by convenience sampling method. Analysis of the data in this study aided by using SPSS 17. The method of data analysis used is multiple linear regression The results showed that the variables of the tax system, taxes and service quality discrimination significant effect on the ethics of tax evasion, while the equity variable has no effect and no significant effect on the ethics of tax evasion. Keywords:ethics perception, tax evation, fairness, taxation systems, the quality of tax service, discrimination